2022
DOI: 10.3390/cells11193052
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of Flavonoid Synthesis in Mushroom Cells

Abstract: Flavonoids are chemical compounds that occur widely across the plant kingdom. They are considered valuable food additives with pro-health properties, and their sources have also been identified in other kingdoms. Especially interesting is the ability of edible mushrooms to synthesize flavonoids. Mushrooms are usually defined as a group of fungal species capable of producing macroscopic fruiting bodies, and there are many articles considering the content of flavonoids in this group of fungi. Whereas the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Flavonoids are a class of yellow pigments that contain a C6–C3–C6 backbone ( Lewandowska et al, 2016 ). Numerous studies have reported the presence of flavonoids in mushroom extracts from a variety of species ( Pukalski and Latowski, 2022 ; Wang et al, 2022a ). It is noteworthy that the total flavonoid content is nearly fifty percent of the total phenolic content, and that their distribution patterns remain the same, although no significant difference was observed between these three mushrooms.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are a class of yellow pigments that contain a C6–C3–C6 backbone ( Lewandowska et al, 2016 ). Numerous studies have reported the presence of flavonoids in mushroom extracts from a variety of species ( Pukalski and Latowski, 2022 ; Wang et al, 2022a ). It is noteworthy that the total flavonoid content is nearly fifty percent of the total phenolic content, and that their distribution patterns remain the same, although no significant difference was observed between these three mushrooms.…”
Section: Resultsmentioning
confidence: 99%
“…The GC-MS method can be used for nonpolar and volatile compounds analysis, such as fatty acids, essential oil and terpene (Jiang et al, 2016). The phenolic compounds like flavonoid only detected by LC-MS method (Pukalski & Latowski, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, however, whether mycelia can produce flavonoids remains controversial. Although flavonoid synthesis has been detected in mycelial cells, it remains unresolved whether fruiting bodies have a similar ability ( Pukalski and Latowski, 2022 ). In this study, the total antioxidant capacity of the fermentation substrate was related to flavonoid abundance.…”
Section: Discussionmentioning
confidence: 99%